Α-Adrenoceptor antagonistic and hypotensive properties of novel arylpiperazine derivatives of pyrrolidin-2-one. Issue 9 (1st May 2015) - Zaręba, Paula; Dudek, Magdalena; Lustyk, Klaudia; Siwek, Agata; Starowicz, Gabriela; Bednarski, Marek; Nowiński, Leszek; Raźny, Katarzyna; Sapa, Jacek; Malawska, Barbara; Kulig, Katarzyna
Graphical abstract: Abstract : Highlights: The series of pyrrolidin-2-one derivatives were synthesized. The compounds obtained were evaluated for their affinity for α1 - and α2 -adrenoceptors. Compound with p K i (α1 ) ⩾6.44 were evaluated in functional bioassays for intrinsic activity at α1A - and α1B -adrenoceptors. Selected compounds were subjected to preliminary in vivo studies. Abstract: This study focused on a series of pyrrolidin-2-one derivatives connected via two or four methylene units to arylpiperazine fragment. The compounds obtained for α1 - and α2 -adrenoceptors were assessed. The compound with highest affinity for the α1 -adrenoceptors was 1-{4-[4-(2-chloro-phenyl)-piperazin-1-yl]-butyl}-pyrrolidin-2-one (10h ) with p K i  = 7.30. Compound with p K i (α1 ) ⩾6.44 were evaluated in functional bioassays for intrinsic activity at α1A - and α1B -adrenoceptors. All compounds tested were antagonists of the α1B -adrenoceptors. Additionally, compounds10e and10h were α1A -adrenoceptors antagonist. The dual α1A -/α1B -adrenoceptors antagonists, compounds10e and10h were also tested in vivo for their hypotensive activity in rats. These compounds, when dosed of 1.0 mg/kg iv in normotensive, anesthetized rats, significantly decreased systolic and diastolic pressure and their hypotensive effects lasted for longer than one hour.